Democratic Backsliding in Africa? Autocratization, Resilience, and Contention - Arriola, Leonardo R.; Rakner, Lise; van de walle, Nicolas (Oxford University Press, 2023)
Why have most African countries not achieved greater political liberalization? What explains the lack of progress toward the ideals of liberal democracy across the region? This book advances ongoing debates on democratic backsliding with specific reference to Africa. In examining how incumbent leaders in African countries attempt to contain societal pressures for greater democracy, the chapters explain how governments go beyond the standard tools of manipulation, such as electoral fraud and political violence, to keep democracy from unfolding in their countries. The book emphasizes two distinct strategies that governments frequently use to reinforce their hold on power, but which remain overlooked in conventional analyses; -the legal system and the international system. It-documents how governments employ the law to limit the scope of action among citizens and civil society activists struggling to expand democratic liberties, including the use of constitutional provisions and the courts. The work further demonstrates how governments use their role in international relations to neutralize pressure from external actors, including sovereigntist claims against foreign intervention and selective implementation of donor-promoted policies. While pro-democracy actors can also employ these legal and international strategies to challenge incumbents, in some cases to prevent democratic backsliding, the book shows why and how incumbents have enjoyed institutional advantages when implementing these strategies through the six country case studies of Ghana, Kenya, Malawi, Uganda, Zambia, and Zimbabwe.